Tracking key CAADP indicators and implementation processes [In the 2022 ATOR] - Collins, Julia; Makombe, Tsitsi; Tefera, Wondwosen; Yamdjeu, Augustin Wambo (AKADEMIYA2063, 2022)
Agriculture is a vital source of livelihoods for more than 60 percent of Africa’s population. Recognizing the need to boost investments and productivity in the sector, in 2003, African leaders adopted the Comprehensive Africa Agriculture Development Programme (CAADP) as the policy framework for revitalizing agriculture and reducing poverty and food insecurity on the African continent. Following a decade of implementing CAADP, the framework gained momentum in 2014, when African heads of state and government adopted the Malabo Declaration on Accelerated Agricultural Growth and Transformation for Shared Prosperity and Improved Livelihoods. Through the Declaration, they recommitted to upholding CAADP principles and values, which include adopting evidence-based planning, policy efficiency, dialogue, review, and accountability and exploiting regional complementarities. They also pledged to increase investment in agriculture, end hunger and halve poverty by 2025, boost intra-African agricultural trade, enhance resilience to climate variability, and strengthen mutual accountability for actions and results by conducting a continental Biennial Review (BR) of progress made in achieving the commitments (AUC 2014).